PENTOPIKALAN DALAM BAHASA PAKPAK-DAIRI - Ida Basaria (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe topicalization in the Pakpak-Dairi language as a pragmaticsyntactic process that changes elements of non-topic into topic. The data were spoken and written data on the use of the Pakpak-Dairi language. They were analyzed by means of the distribution method using the substitution and form-changing techniques. The results of the study are as follows. First, in the Pakpak-Dairi language there are core arguments and those in the form of the oblique relation that can be emphasized through fronting. The emphasis of core arguments is made through topicalization. On the other hand, the emphasis of oblique relation arguments is made not through topicalization, but through fronting or left-dislocation. Second, the Pakpak-Dairi language has the V-O-S word order as an unmarked construction and the topicalization (O-S-V) form as a marked construction. Therefore, it can be concluded that the Pakpak Dairi language belongs to the typology group of languages not emphasizing the subject and topic.